Industrial training report: Hospital Pakar Kanak-Kanak (HPKK), UKM / Balqis Nabila Ibrahim - Ibrahim, Balqis Nabila (Universiti Teknologi MARA, Negeri Sembilan, 2024)
By exposing students to authentic work settings, enabling them to apply theoretical knowledge to real-world scenarios, and keeping them aware of the most recent technological advancements and industry information, industrial training seeks to improve students' educational experiences. It also encourages cooperation between academia and business, facilitating the sharing of resources and ideas. Overall, by combining classroom instruction with practical experience, these goals equip students for prosperous careers. There are lots of main goals through these programmes. By applying the ideas, they have studied in class to real-world scenarios, students can strengthen their comprehension. Besides, students acquire knowledge about ethical standards, customs, and practices specific to their industries. On the other hand, through firsthand experience with business procedures, the training improves both hard and soft skills.